2017
DOI: 10.7860/jcdr/2017/25771.9964
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bromelain along with Trypsin, Rutoside Trihydrate Enzymes and Diclofenac Sodium Combination Therapy for the treatment of TMJ Osteoarthritis - A Randomised Clinical Trial

Abstract: Introduction: Osteoarthritis (OA) is a degenerative disorder characterized by chronic inflammatory response of cartilage and articular surface involving Temporomandibular Joint (TMJ). Pain as one of the major symptom of osteoarthritis affects the quality of life and is usually managed by Non Steroidal Anti Inflammatory Drugs (NSAIDs) such as diclofenac sodium. Bromelain, trypsin and rutoside trihydrate formulation can be used to treat this disease because of anti-inflammatory and anti-oxidant effects. Aim:To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Bromelain contributes to decreasing oxidative stress and the expression of inflammatory mediators, including bradykinin, thromboxane A2, and PGE 2 [190,191]. Recent studies prove that using bromelain in combination therapy with other nutraceuticals, such as diclofenac sodium, rutin, trypsin, or turmeric, results in significantly enhanced efficacy in the treatment of degenerative joint pain diseases [191][192][193][194].…”
Section: Osteoarthritismentioning
confidence: 99%
“…Bromelain contributes to decreasing oxidative stress and the expression of inflammatory mediators, including bradykinin, thromboxane A2, and PGE 2 [190,191]. Recent studies prove that using bromelain in combination therapy with other nutraceuticals, such as diclofenac sodium, rutin, trypsin, or turmeric, results in significantly enhanced efficacy in the treatment of degenerative joint pain diseases [191][192][193][194].…”
Section: Osteoarthritismentioning
confidence: 99%
“…Reports from preliminary clinical studies have indicate the potential safety and efficacy of bromelain-based enzymatic debridement in chronic wounds(6) and deep burn injuries (7). In addition, reports have shown that anti-inflammatory and analgesic characteristics of bromelain could be useful in the treatment of several chronic inflammatory disorders as osteoarthritis and rheumatoid arthritis (8–10). Recent studies have evaluated the clinical implications of bromelain in reducing postoperative inflammatory complications after third molar surgery (11,12), but the results are contrasting (13).…”
Section: Introductionmentioning
confidence: 99%
“…This extract importantly alleviates pain and edema and shortens healing time compared to conventional treatments [47,48]. Bromelain induces the reduction of inflammatory and pain mediators, acting as an anti-inflammatory agent in many conditions, attenuating asthma [49], rheumatoid arthritis and osteoarthritis [50].…”
Section: Bromelainmentioning
confidence: 99%
“…Enzymatic debridement reduces wound healing time, morbidity and mortality in severely burned patients. Bromelain has very low toxicity and is not carcinogenic or teratogenic [32,47,48,50].…”
Section: Bromelainmentioning
confidence: 99%